Learning Outcomes of an Educational Leadership Cohort Program - Pamela D. Tucker; Cheryl B. Henig; Michael J. Salmonowicz (Educational Considerations, 2005)
Over the past three decades, demands on public schools have increased dramatically with a direct impact on the expectations of principals.